2015
DOI: 10.18632/oncotarget.5345
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic regulation of AMPK in breast cancer affects cytoskeletal properties involved with microtentacle formation and re-attachment

Abstract: The presence of tumor cells in the circulation is associated with a higher risk of metastasis in patients with breast cancer. Circulating breast tumor cells use tubulin-based structures known as microtentacles (McTNs) to re-attach to endothelial cells and arrest in distant organs. McTN formation is dependent on the opposing cytoskeletal forces of stable microtubules and the actin network. AMP-activated protein kinase (AMPK) is a cellular metabolic regulator that can alter actin and microtubule organization in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Conversely, we found that treatment with AMPK inhibitor Compound C ( Figure 4C ) or inhibition of AMPK by shRNA-mediated knockdown ( Figure 4D ) effectively rescues decreased cell viability upon combined treatment with Physcion + DHA. In addition, combined treatment with Physcion and AMPK activator A769662 [ 14 16 ] results in synergistic inhibition of cell viability ( Figure 5A ) and induction of apoptosis in K562 cells ( Figure 5B ), as well as inhibition of cell viability of diverse leukemia cells including KG1a, HEL and Molm14 ( Figure 5C ). Furthermore, we previously demonstrated that 6PGD-mediated production of ribulose-5-phosphate (Ru-5-P) inhibits AMPK activation by disrupting the active LKB1 complex [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, we found that treatment with AMPK inhibitor Compound C ( Figure 4C ) or inhibition of AMPK by shRNA-mediated knockdown ( Figure 4D ) effectively rescues decreased cell viability upon combined treatment with Physcion + DHA. In addition, combined treatment with Physcion and AMPK activator A769662 [ 14 16 ] results in synergistic inhibition of cell viability ( Figure 5A ) and induction of apoptosis in K562 cells ( Figure 5B ), as well as inhibition of cell viability of diverse leukemia cells including KG1a, HEL and Molm14 ( Figure 5C ). Furthermore, we previously demonstrated that 6PGD-mediated production of ribulose-5-phosphate (Ru-5-P) inhibits AMPK activation by disrupting the active LKB1 complex [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…JMJD1A protein levels in certain cytoplasmic locations is dependent upon cell growth rate and Hsp90 chaperone activity [ 36 , 37 , 38 ], which also interferes with JMJD1A stability and activity [ 36 ]. Kasiolius et al (2014) showed that JMJD1A deficiency in rats resulted in cytoskeleton abnormalities, which in turn was associated with metastatic potential, more aggressive tumors and decreased global survival and disease-free survival in breast cancer patients [ 39 ]. This study also showed an association between ADM protein expression and lymph node metastasis, so that high expression increases lymph node metastasis risk by 9 fold.…”
Section: Discussionmentioning
confidence: 99%
“…Breast carcinoma cells suspended above weakly adhesive substrates produce cytoneme-like long and dynamic membrane tubular structures, the length of which increased significantly under the influence of cytochalasin D or latranculin A. Since the formation of blood-borne metastases depends on the interaction of cells with substrates and other cells, long sticky membrane structures in unattached transformed epithelial cells of the breast can play an important role in the spread of breast cancer metastases [104,105]. In primary spleen lymphocytes and Bal 17 cells, the binding of the B cell antigen receptor by immunoglobulin M (IgM), an antigen surrogate, led to the appearance of very long threadlike structures [106].…”
Section: Cytonemes In Embryonic Blood and Other Eukaryotic Cellsmentioning
confidence: 99%